2021
DOI: 10.1111/bjh.17395
|View full text |Cite
|
Sign up to set email alerts
|

Real‐life targeted next‐generation sequencing for lymphoma diagnosis over 1 year from the French Lymphoma Network

Abstract: Summary As the impact of targeted next‐generation sequencing (TNGS) on daily diagnosis has not been evaluated, we performed TNGS (46 genes) on lymphomas of unclear subtype following expert haematopathological review. The potential impact on patient care and modifications of final diagnosis were divided into major and minor changes according to the European Society of Medical Oncology (ESMO) guidelines. Among 229 patients [19 primary central nervous system lymphomas (PCNSL), 48 large B‐cell lymphomas (LBCLs), 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Concerning AITL, most studies concern nodal locations, in which mutations of TET2 (52-76%), IDH2 (20-45%), DNMT3A (30-40%) and RHOA G17V (28-70%) seem frequent [11][12][13][14][15][16] . The only study currently published in cutaneous localizations is the one of Leclaire Alirkilicarslan et al, which included 41 patients and found IDH2 R172K/S and RHOA G17V mutations in 19% and 78% of cases respectively using PCR 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning AITL, most studies concern nodal locations, in which mutations of TET2 (52-76%), IDH2 (20-45%), DNMT3A (30-40%) and RHOA G17V (28-70%) seem frequent [11][12][13][14][15][16] . The only study currently published in cutaneous localizations is the one of Leclaire Alirkilicarslan et al, which included 41 patients and found IDH2 R172K/S and RHOA G17V mutations in 19% and 78% of cases respectively using PCR 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Leclaire Alirkilicarslan et al found 78% of RHOA G17V and 19% of cases with IDH2 R172 substitutions using www.nature.com/scientificreports/ PCR in a cohort of cAITL. In nodal AITL, mutations are much more frequent 11,12,15 ; TET2 SNV (76%), RHOA G17V (60-78%), and IDH2 R172 substitutions (19.5%). In the present study, the percentage of mutated cases was lower than described in the literature, and no IDH2 pathogenic variants were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These 10 cases were classified as MZL ( n = 7), LPL ( n = 2), and HCL‐v ( n = 1). Bommier et al 15 reported diagnostic impact in 73% (168/229 cases) of patient samples using a 46 custom‐made gene panel. The majority of these cases ( n = 144) were confirmatory of the diagnosis and there were no cases of unclassified to classified lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, characteristic mutational profiles in different types of lymphomas and probable prognostic algorithms based on mutational findings are being increasingly reported in the literature. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Specific mutations may aid in diagnostic refinement and serve as inclusion or exclusion criteria to protocolled treatment strategies 19,20 as well as trial stratification.…”
Section: Introductionmentioning
confidence: 99%